Mudanças nas preferências do Banco Central: um estudo empírico para o Brasil - Medeiros, Rennan Kertlly de (2018)
This dissertation aims to study the behavior of the preferences parameters of the Central Bank of Brazil (BCB), in the period between 2000.T1 and 2017.T4. To accomplish this purpose, we assume that Brazil’s monetary policy is deﬁned in an optimized way, then we obtain the parameters of the political function from the estimation of the macroeconomic model with expectations backward-looking and the preferences of the Central Bank. The econometric approach used is based on Bayesian MCMC estimation supported by the Kalman ﬁlter. Our results indicate that Central Bank’s preferences have been unstable over time, with ﬂuctuations after the ending of the term of BCB’s chairman and during the 2008 international crisis.